2017
DOI: 10.1021/acscatal.7b02570
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Coupling among Metal and Oxide Phases during CO Oxidation on Partially Reduced PdO(101): Influence of Gas-Phase Composition

Abstract: We used direct-rate measurements and reflection absorption infrared spectroscopy (RAIRS) to investigate CO oxidation on a PdO(101) film at 450 K and focused on characterizing how the gas-phase composition (O 2 + CO) influences the reaction kinetics and the coupling between the reaction and the surface phases that develop. We find that chemisorbed O atoms on Pd(111) are intrinsically more reactive than PdO(101) and that CO oxidation rates can be as much as 2−3 times higher on Pd(111) compared with PdO(101) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 44 publications
4
36
0
Order By: Relevance
“…The CO oxidation (2 CO + O 2 → CO 2 ) on platinum group metal surfaces, such as palladium, has been intensively studied during decades, due to its enormous technological impact, and also as a model heterogeneous gas/surface catalytic reaction. 1 In the early times, 2,3 Surface Science experiments carried out in Ultrahigh Vacuum (UHV) played an essential role in the basic understanding of the CO oxidation process, but a much deeper atomic-scale insight is being lately gained through surface sensitive techniques that operate at millibar and bar pressures, such as high-pressure Scanning Tunneling Microscopy (STM), 4,5 Near-Ambient Pressure X-ray photoemission spectroscopy (NAP-XPS), [6][7][8] infrared reflection absorption spectroscopy, [9][10][11][12][13] and high-energy surface X-ray diffraction. [14][15][16][17][18][19][20][21][22][23] All these studies agree in the fundamental picture, namely the abrupt transition at the "ignition" temperature, from the low-temperature oxidation stage, when CO covers (or "poisons") the catalytic surface, to the high-temperature activity stage, when the CO-poisoning layer is displaced by chemisorbed oxygen, preceding the build-up, first, of two-dimensional (2D) surface oxides, and last, of bulk oxides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CO oxidation (2 CO + O 2 → CO 2 ) on platinum group metal surfaces, such as palladium, has been intensively studied during decades, due to its enormous technological impact, and also as a model heterogeneous gas/surface catalytic reaction. 1 In the early times, 2,3 Surface Science experiments carried out in Ultrahigh Vacuum (UHV) played an essential role in the basic understanding of the CO oxidation process, but a much deeper atomic-scale insight is being lately gained through surface sensitive techniques that operate at millibar and bar pressures, such as high-pressure Scanning Tunneling Microscopy (STM), 4,5 Near-Ambient Pressure X-ray photoemission spectroscopy (NAP-XPS), [6][7][8] infrared reflection absorption spectroscopy, [9][10][11][12][13] and high-energy surface X-ray diffraction. [14][15][16][17][18][19][20][21][22][23] All these studies agree in the fundamental picture, namely the abrupt transition at the "ignition" temperature, from the low-temperature oxidation stage, when CO covers (or "poisons") the catalytic surface, to the high-temperature activity stage, when the CO-poisoning layer is displaced by chemisorbed oxygen, preceding the build-up, first, of two-dimensional (2D) surface oxides, and last, of bulk oxides.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Pd, the CO oxidation reaction has been investigated on a variety of high and low symmetry crystal surfaces under reaction conditions. [4][5][6][7][8]10,13,[21][22][23][24][25][26][27][28] This will help to separately understand the catalytic performance at crystal planes that shape technologically relevant nanoparticles. However, given the variety of reaction parameters and experimental constraints, comparative in-situ investigations among different surface orientations would be better suited.…”
Section: Introductionmentioning
confidence: 99%
“…To study Models I and II, we used both the qualitative methods of theory of dynamical systems and numerical methods, which include the methods of continuation of the steady state and limit cycle on the parameter. The values of the rate constants of steps were previously determined in our works . The rate constants of steps were varied according to the experimental and density functional theory (DFT) data, which demonstrated that the rate of CO oxidation over PdO depends on the case where surface oxide, epitaxial oxide, or polycrystalline bulk oxide are considered.…”
Section: Mathematical Modelingmentioning
confidence: 99%
“…The values of the rate constants of steps (1)-(3) were previously determined in our works. 9,10 The rate constants of steps (4)-(6) were varied according to the experimental 33 and density functional theory (DFT) data, 34,35 which demonstrated that the rate of CO oxidation over PdO depends on the case where surface oxide, epitaxial oxide, or polycrystalline bulk oxide are considered. In Ref.…”
Section: Kinetic Modelmentioning
confidence: 99%
See 1 more Smart Citation